Regulation of the heat shock transcription factor Hsf1 in fungi: implications for temperature-dependent virulence traits. Issue 5 (18th April 2018) - Veri, Amanda O; Robbins, Nicole; Cowen, Leah E
Abstract: The impact of fungal pathogens on human health is devastating. For fungi and other pathogens, a key determinant of virulence is the capacity to thrive at host temperatures, with elevated temperature in the form of fever as a ubiquitous host response to defend against infection. A prominent feature of cells experiencing heat stress is the increased expression of heat shock proteins (Hsps) that play pivotal roles in the refolding of misfolded proteins in order to restore cellular homeostasis. Transcriptional activation of this heat shock response is orchestrated by the essential heat shock transcription factor, Hsf1. Although the influence of Hsf1 on cellular stress responses has been studied for decades, many aspects of its regulation and function remain largely enigmatic. In this review, we highlight our current understanding of how Hsf1 is regulated and activated in the model yeast Saccharomyces cerevisiae, and highlight exciting recent discoveries related to its diverse functions under both basal and stress conditions. Given that thermal adaption is a fundamental requirement for growth and virulence in fungal pathogens, we also compare and contrast Hsf1 activation and function in other fungal species with an emphasis on its role as a critical regulator of virulence traits. Abstract : The authors describe how the heat shock responsive transcription factor Hsf1 is regulated in diverse fungal species, and highlight recent discoveries related to its role in governing fungal virulence traits.